Communication Skills of Anatolian Vocational Health High School Students - Sevgi Gaskar; Nurcan Özyazıcıoğlu (Güncel Pediatri)
Introduction: This research is conducted to determine the level of communication and influencing skills students studying in classes 9 and 12 in Bursa Anatolian Vocational Health High School. Materials and Methods: The research group consisted of 218 students. Data communication with the inventory collected with a questionnaire containing demographic characteristics of the students. Percentile of the data analysis, Kruskal-Vallis, correlation test was used. Results: The mean score of students’ communicative skills inventory was 164.61+17.20. No significant difference was found between success in school and communication skills with the students’ gender, number of siblings. While there is no difference between free time activities watching TV and communication skills of students, there is a significant difference between the habit of using the computer and communication skills of students between the total score and subscales. Conclusions: Students’ communication skills scores are higher in girls than in boys, school achievement and communication skills scores increased parallel to the increase number of siblings. The habit of reading a book, while the positive affect on the mental score communication skills, scores of all the communication skills of students negative affects the increase in computer usage time. Effect on student reading scores for class communication skills to improve communication skills courses put the quality and increasing the recommend hours. (The Journal of Current Pediatrics 2014;1:20-5)